135 Cardiovascular Complications in Sickle Cell Disease. (6th June 2015) - Ako, Emmanuel; Walker, Malcolm
Abstract : Introduction: Sickle cell disease (SCD) is a genetic disorder affecting the production of haemoglobin (Hb). It has life-long consequences with multi-organ involvement including the cardiopulmonary circulation and an increased mortality. Although all SCD patients share the same genetic defect, the phenotype varies. This suggests other factors, unrelated to the Hb mutation, play an important role particularly in later decades. This retrospective study examined patient survival attending a specialist tertiary centre in the United Kingdom based on Tricuspid Regurgitant Jet Velocity (TRJ) measured by echocardiography and associated laboratory studies. Method: A retrospective analysis of TRJ and diastolic function (lateral E/E' ratio) assessed by echocardiography in 127 intensively treated steady-state SCD patients (mean age 40 +/- 12 years) screened for cardiovascular complications. Laboratory studies were also analysed. Results: The clinical characteristics of patients in this study is summarised in Table 1 . 15% of patients had a TRJ between 2.6–2.99 m/s and 9% with TRJ >3.0 m/s. 11% of patients had diastolic dysfunction using lateral E/E' ratio. When compared to patients with a TRJ <2.5 m/s, the risk of death is 4 times higher in the 2.6–2.99 TRJ group and 24 times higher in the > 3.0 TRJ group. See Figure 1 . Lateral E/E' ratio (beta = 0.88, p = 0.015), left atrial area (beta = 0.38, p < 0.001) and microalbuminuria (beta = 0.10, p = 0.05) were independently associated with TRJ. Conclusion: Mortality in SCD patients with raised TRJ remains high despite intensive therapy, such as exchange transfusion, directed at correcting Hb. Screening with echocardiography remains an important tool in identifying high-risk patients. Additional therapies directed at the premature ageing of the cardiopulmonary circulation are urgently needed.